ANALISIS IMPELENTASI PENDIDIKAN KARAKTER (NILAI TOLERASI ,PEDULI SOSIAL,RELEGIUS DAN KEBERSAMAAN) DI MAYARAKAT DESA RANSI DAKAN - Hartini, Agnesia; Nada, Silvester; Djabar, Sinci Namang (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to describe the implementation of character education (values of tolerance, social care, religion and togetherness) in the village community. The research analyzes the implementation of character education in the village community with a focus on the values of tolerance, social care, religion and togetherness. Through a qualitative approach, this article explores how villages manage diversity, promote social care, permeate religious values and build a sense of community. The analysis shows that despite positive efforts, there are also challenges in implementing these values. Inter-ethnic conflict, lack of participation in social activities, and inequality in religious understanding are some aspects that need attention. In this context, recommendations are given to strengthen character education initiatives, expand community participation and build inter-group dialogue to strengthen character values in village communities. This article is expected to provide insights for readers on the dynamics of character education implementation in the ransi dakan village environment.Keywords: Implementation of character education, tolerance values, social care values, and the Ransi Dakan community